The Analysis of the Use of PjBL in Mobile Application Development with Artificial Intelligence Library in XIF1 SMAN 3 Surakarta - Nugroho, Yunanto Dwi; Hatta, Puspanda; Jumari (Journal of Global Hospitality and Tourism Technology, 2025)
Indonesia continues to improve the quality of education in order to compete regionally and globally. This research was conducted at SMA Negeri 3 Surakarta on students of class XI F1, consisting of 36 students. The focus of the research is to evaluate the effectiveness of Project Based Learning (PjBL) method in learning Mobile Application Development with Artificial Intelligence Library. Data were collected through classroom observation, interviews with Informatics teachers, and questionnaires to students. The results showed that the PjBL method was effective in improving students' understanding of the material taught. In addition, this method also helps students develop important skills, such as collaboration, problem solving, and project management. Students showed significant improvement in working in groups, sharing tasks, and solving problems. Thus, PjBL not only improves academic understanding, but also skills that are useful for students' future.